2004
DOI: 10.1002/cne.20348
|View full text |Cite
|
Sign up to set email alerts
|

Single-axon tracing and three-dimensional reconstruction of centre médian-parafascicular thalamic neurons in primates

Abstract: The axonal projections from the centre median (CM)/parafascicular (Pf) thalamic complex in squirrel monkeys were studied after microiontophoretic injections of biotinylated dextran amine under electrophysiological guidance. A total of 29 axons connected to their parent cell body were entirely reconstructed from serial sections with a camera lucida. Our investigation shows that the CM and Pf nuclei in primates comprise three types of projection neurons: (1) neurons that innervate densely and focally the striatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 54 publications
7
99
1
2
Order By: Relevance
“…The dendrites of CL neurons adhered to the bushy architecture typical of thalamic relay neurons, whereas the dendrites of Pf neurons were reticular-like, in agreement with previous studies (Scheibel and Scheibel, 1967;Jones, 1985;Sugiyama et al, 1992;Deschênes et al, 1996a,b;Parent and Parent, 2005). The distinct firing properties of CL and Pf neurons in vivo might reflect these conspicuously different dendritic arbors.…”
Section: Dendritic Architectures Of CL and Pf Neurons Are Distinctsupporting
confidence: 90%
“…The dendrites of CL neurons adhered to the bushy architecture typical of thalamic relay neurons, whereas the dendrites of Pf neurons were reticular-like, in agreement with previous studies (Scheibel and Scheibel, 1967;Jones, 1985;Sugiyama et al, 1992;Deschênes et al, 1996a,b;Parent and Parent, 2005). The distinct firing properties of CL and Pf neurons in vivo might reflect these conspicuously different dendritic arbors.…”
Section: Dendritic Architectures Of CL and Pf Neurons Are Distinctsupporting
confidence: 90%
“…The morphology of the biocytin-labeled Pf cells sampled in this study matched that previously reported for Pf cells in rodents and other species using various single cell labeling techniques (Hazlett et al, 1976;Sugiyama et al, 1992b;Fenelon et al, 1994;Deschenes et al, 1995;Deschenes et al, 1996;Vercelli et al, 2003;Parent and Parent, 2005). Specifically, Pf cells exhibited long, unramifying primary dendrites unlike the compact, bushy dendritic trees which characterize neighboring thalamic relay neurons in the rat (Harris, 1986;Sawyer et al, 1989;Bartlett and Smith, 1999;Li et al, 2003).…”
Section: Conclusion Heterogeneity Of Electrophysiological Propertiessupporting
confidence: 77%
“…In contrast, anatomical studies have long recognized that many cells in the Pf have a distinct morphology compared with thalamic relay nuclei (Hazlett et al, 1976;Hazlett and Hazlett, 1977;Pearson et al, 1984;Parent and Parent, 2005). Typically, they contain long unbranching processes in their proximal dendritic trees.…”
Section: Introductionmentioning
confidence: 99%
“…As the centro-median thalamic nucleus, sending back its efferents to the sensorimotor territories of the striatum and to the motor and premotor cortical areas, is predominantly involved in the motor basal ganglia-thalamocortical loop (Alexander et al, 1990;Parent and Parent, 2005), this altogether suggests that the motor subcortical loop is the most affected by the degenerative process at this stage of the disease.…”
Section: Discussionmentioning
confidence: 99%